Effects of drying methods on active odorants, phytochemicals and antioxidant properties of Litsea petiolata Hook. f. leaves locally used as a substitute to male giant water bugs in pungent chili pastes - Sangsila, A.; Jorjong, S.; Chumroenphat, T. (International Journal of Agricultural Technology, 2021)
The plant species Litsea petiolata Hook. f. has been traditionally used as a flavouring ingredient in chili paste as a substitute to male giant water bugs in many parts of Thailand and some Southeast Asian countries, due to the male giant water bug-like fragrance of its various parts. However, the knowledge about its odor, phytochemical quality, and antioxidant activity of this plant has not been known widely. The current study compared the odorant profiles between male giant water bugs and dried leaves of L. Petiolata and compared the phytochemicals and antioxidant properties of the leaves from three different drying methods. Nine odorants were common in male giant water bugs and dried leaf samples, with undec-10-en-2-one and undecanone detected at high levels, thus serving as important odorant contributors. The best efficient way among the three methods to keep the odorants, phenolic acids (chologenic, gallic, rutin and ferulic acid), flavonoids (catechin hydrate, p-coumaric acid and myracetin), and vitamin C was drying in the frozen temperatures. Moreover, the leaves dried by the cool method contained high amount of phenolic acids, flavonoid, and the quantity of antioxidant, as compared to other drying methods. The research results revealed that L. petiolata’s leaves were rich in phytochemicals and antioxidant capacities which provided benefits to people. Moreover, It is elucidated the contribution for drying processes, and the stability of other qualifications of the plants, such as the biological components and the number of antioxidant.